ANALISIS PEMANFAATAN WIRELESS HOTSPOT BAGI PEMENUHAN KEBUTUHAN INFORMASI PEMUSTAKA PADA PERPUSTAKAAN DAERAH KABUPATEN PURWAKARTA - DIDIH Aditiyawarman (LPPM Universitas Bina Sarana Informatika, 2015)
Utilization of wireless technology is now used in almost all fields, education, businesses, organizations, companies and others. With the wireless technology, Internet access becomes easier and faster, can be done anytime and anywhere. One of these is the use of technology in the library. Hostpot wireless services especially in Purwakarta District Library aims to improve service to the visitors and to facilitate the search and fulfillment information needed by the visitors. Apart from reading books, with this facility, the visitors can browse the information they need through the internet in the form of digital data by using wireless hotspot locations contained in the library. In the present study tested whether the use of wireless hotspots as a means of access to digital data have a relationship and affect the fulfillment of information needs of the visitors. The study was conducted by using a questionnaire given to the visitors for later processing performed to test the hypothesis that the data taken using the SPSS application. From the results of the study will be determined how the use of wireless hostpsot towards fulfillment of the visitors so that information can be used as input for the library.